To Mix or Not to Mix: Details of Magma Storage, Recharge, and Remobilization during the Pacheco Stage at Misti Volcano, Peru (≤21–2 ka) - Takach, Marie K. (2024)
We investigate ten of the most recent tephra-fall deposits emplaced between ≤21 and 2 ka from the Pacheco stage of Misti volcano, Peru, to elucidate magma dynamics and explosive eruption triggers related to magma storage, recharge, and remobilization. Whole-rock, glass, and mineral textures and compositions indicate the presence of broadly felsic, intermediate, and mafic magmas in a chemically and thermally stratified magma storage system (Zones 1–3) that interact to differing extents prior to eruption. Intermediate magmas are defined by plagioclase + amphibole + two-pyroxenes + Fe-Ti oxides and phase equilibria indicate they formed at ~300 to 600 MPa and ~950°C to 1000°C. Intermediate magmas dominate the Pacheco stage and either erupted alone as hybridized magmas or mingled with minor volumes of cool felsic magmas (~800°C) in which only plagioclase + Fe-Ti oxides are stable. Felsic magmas do not exclusively comprise any tephra-fall deposit emplaced during the Pacheco stage but were remobilized by recharge and mixing with intermediate magmas in order to erupt. Furthermore, felsic-hosted amphibole cognate to the intermediate magmas are reacted despite the felsic magmas being water saturated, which suggests they are staged above the amphibole stability limit (≤200 MPa). The cryptic presence of mafic magmas is indicated by high-An plagioclase cores (An₇₄₋₈₈), rare anhedral olivine (Fo₇₇₋₈₀), and possibly high Mg# augite and amphibole (up to Mg# 84 and 77, respectively). The dearth of basalt to basaltic andesite melts recorded in erupted glasses and exclusivity of high-An plagioclase to crystal cores signals mafic magmas are staged deeper in the crust than the intermediate magmas. Periodic interactions between these magmas tracked via glass compositions and crystal exchange reveal an alternation between the production of mingled magmas and their eruption shortly after a recharge event, followed by a period of homogenization and eruption of hybridized magmas. As such, we identify magma recharge as a key mechanism by which half of the explosive eruptions were triggered in the Pacheco stage. A >100°C increase in Misti’s fumarole temperatures from 1967 to 2018 coincident with changes in fumarolic gas compositions is consistent with degassing of a mafic recharge magma, signaling that Misti could produce similar explosive eruptions in the future.